The transparency obligations of political parties under Spanish law - GONZÁLEZ-JULIANA, Álvaro (Revista Jurídica Portucalense, 2025)
This article examines the legal framework for political parties within the subjective scope of the Spanish Law on Transparency and Access to Public Information. Although included in its scope of application, parties are only subject to limited active disclosure obligations, with no obligation to respond to requests for information from citizens. The theoretical and practical analysis of the parties' disclosure obligations and their compliance reveals weaknesses in the current model, compromising the effectiveness of transparency as a tool for ensuring true accountability and preventing corruption within political formations.